Method for preparing lithium-containing silicon metal, lithium-containing silicon metal, lithium-containing SiO and their applications
Patent Information
- Application Number
- JP2022576841
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-04-21
- Filing Date
- 2022-04-26
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-04-26
Smart Images

Figure 0007640588000002 
Figure 0007640588000003 
Figure 0007640588000004
Abstract
Description
[Technical field]
[0001] This application claims priority to Chinese Patent Application No. 2022104240244, entitled "Method for preparing lithium-containing metal silicon, lithium-containing metal silicon, lithium-containing SiO and its application," filed with the Patent Office of the State Intellectual Property Administration of China on April 21, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a method for preparing lithium-containing metallic silicon, lithium-containing metallic silicon, and further to lithium-containing SiO obtained based on the lithium-containing metallic silicon and applications thereof. [Background technology]
[0003] In recent years, the range of applications of SiO as a deposition material or new energy material has been expanding. For example, in order to increase the coulombic efficiency of lithium-ion batteries, SiO is used as the negative electrode material of lithium-ion batteries. In the prior art, a lithium doping technique is usually proposed in which metallic lithium or lithium salt is directly embedded in the finished SiO product by high-temperature reaction. Specifically, an invention patent with publication number CN105789577A discloses a method for preparing a silicon negative electrode material for lithium-ion batteries and the silicon negative electrode material, and SiO 2 It has been proposed to embed silicon in the SiO2 and coat it with lithium titanate, and an invention patent with publication number CN110993949A discloses an anode material with multiple coating structures, its preparation method and use, which includes lithium-containing SiO2 and a lithium salt coating layer, a carbon coating layer and a polymer coating layer coated on the surface of the SiO2 in order. However, the applicant has found, after searching and analyzing a large amount of information, that these lithium doping technologies all perform doping treatment based on the finished SiO2 product, and generally have the disadvantages of high process implementation cost, high process implementation risk and non-uniform lithium distribution.
[0004] In light of the above circumstances, the applicant has decided to seek technical solutions to solve the above technical problems based on the inventor's many years of dedicated research experience in both the fields of silicon-based materials and lithium-ion batteries. Summary of the Invention
[0005] In view of this, the present invention aims to provide a method for preparing lithium-containing metallic silicon, lithium-containing metallic silicon, lithium-containing SiO and their applications, in which the raw materials used are abundant and easy to obtain, and have low costs, the preparation means used are simple and easy to implement, which is conducive to large-scale production and application, and can reduce production risks, and the Li in the obtained lithium-containing metallic silicon and lithium-containing SiO is uniformly distributed.
[0006] The technical solutions used in the present invention are as follows:
[0007] A method for preparing lithium-containing metallic silicon, the raw material being SiO 2 Contains ore particles and reducing agent, SiO 2 At least a portion of the ore particles and the reducing agent undergo a heating and reducing reaction in a reduction furnace to obtain a silicon melt, and the raw material further contains a Li source additive, and in the heating and reducing reaction, at least a portion of the Li source in the Li source additive forms a lithium-silicon alloy with the silicon melt to obtain lithium-containing metallic silicon.
[0008] Preferably, the SiO 2 The ore particles are lithium-containing SiO 2 The lithium-containing SiO 2 The ore particles are obtained by crushing, screening and / or flotation of Li-bearing minerals, said Li-bearing minerals including lithium-bearing pyroxene and / or lithium mica and / or petalite and / or amblygonite and / or eucryptite.
[0009] Preferably, the SiO 2 SiO in ore particles 2The weight ratio of SiO is 30 to 99 wt %, and / or 2 The average particle size of the ore particles is less than 10 mm.
[0010] Preferably, the weight ratio of the Li source additive in the raw material is 0.05 to 35 wt %, and / or the Li source additive is Li and / or Li 2 O and / or Li 2 CO 3 and / or LiOH and / or LiH and / or LiF and / or Li 2 SiO 4 and / or a lithium alloy, and / or the reducing agent comprises a C source reducing agent, an Al source reducing agent, or an Mg source reducing agent, and the SiO 2 They are used to carry out carbothermic, aluminothermic, and magnesothermic reduction reactions corresponding to ore particles, respectively.
[0011] Preferably, the melt of the lithium-containing metallic silicon is transferred to an ingot-forming vessel, and the melt in the ingot-forming vessel is cooled to obtain solid lithium-containing metallic silicon.
[0012] Preferably, the lithium-containing metal silicon is prepared by the above-mentioned preparation method, and the lithium-containing metal silicon includes a lithium-silicon alloy and a lithium silicate.
[0013] Preferably, the lithium-containing silicon metal and SiO 2 The lithium-containing metallic silicon is at least partially converted into the SiO 2 The lithium-containing SiO is obtained by disproportionation sublimation reaction with the powder.
[0014] Preferably, the lithium-containing metal silicon is pre-pulverized to obtain lithium-containing metal silicon powder, and the lithium-containing metal silicon powder and the SiO 2After the powders are mixed, they are placed in a crucible, and the crucible is placed in a vacuum deposition furnace to carry out the disproportionation sublimation reaction. The lithium-containing SiO gas produced by the disproportionation sublimation reaction is condensed to form a lump of lithium-containing SiO.
[0015] Preferably, the lithium-containing SiO is pulverized to obtain a lithium-containing SiO powder, and at least a part of the outer surface of the lithium-containing SiO powder is coated with a carbon coating layer to obtain a lithium-containing SiO powder including a carbon coating layer.
[0016] Preferably, the application of the lithium-containing SiO as described above is such that the lithium-containing SiO powder containing the carbon coating layer is used as an active material raw material for the preparation of a negative electrode piece for a battery.
[0017] In the present invention, SiO 2 Minerals (preferably Li-containing SiO 2 In the specific implementation, a Li source additive is added to the raw material, and during the heating and reducing reaction, at least a part of the Li source in the Li source additive forms a lithium-silicon alloy with the silicon melt to obtain lithium-containing metallic silicon, and in the subsequent application, the lithium-containing metallic silicon and SiO 2 Based on the disproportionation sublimation reaction with lithium-containing SiO powder, lithium-containing SiO can be prepared, which can be directly used as an active material source for making battery pole pieces after being coated with carbon by known processes.
[0018] The raw materials used in the present invention are abundant and easily available, and the cost is low; the preparation means used are simple and easy to implement, which is conducive to large-scale production and application and can reduce production risks; and Li in the obtained lithium-containing metallic silicon and lithium-containing SiO is uniformly distributed; when the lithium-containing SiO with a carbon coating layer provided in the present application is used as an active material raw material for preparing a negative electrode piece for a battery, the battery can exhibit higher capacity and initial coulombic efficiency. [Brief description of the drawings]
[0019] [Figure 1] 4 is a photograph showing a state in which a heating reduction reaction is carried out in a reduction furnace in a specific embodiment of the present invention. [Diagram 2] 1 is a photograph of the finished lithium-containing silicon metal product prepared in a specific embodiment of the present invention. [Diagram 3] 1 is a photograph of a finished lithium-containing silicon metal product prepared in another specific embodiment of the present invention. [Figure 4] 1 is a photograph of the finished lithium-containing SiO2 prepared in accordance with a specific embodiment of the present invention. [Diagram 5] 1 is an XRD scan of lithium-containing SiO2 ore particles employed in a specific embodiment of the present invention; [Figure 6] 1 is an XRD scanning photograph of lithium-containing silicon metal prepared in a specific embodiment of the present invention. [Figure 7] 1 is an XRD scan of lithium-containing SiO prepared in accordance with a specific embodiment of the present invention; [Figure 8] 2 is a scanning electron microscope (SEM) photograph of a negative electrode piece of a button battery according to a specific embodiment of the present invention. [Figure 9] 4 is a capacity test graph of a button battery according to a specific embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] This embodiment discloses a method for preparing lithium-containing metallic silicon, and the raw material is SiO 2 Contains ore particles and reducing agent, SiO 2 At least a part of the ore particles and the reducing agent are subjected to a heating and reducing reaction in a reduction furnace to obtain a silicon melt, and the raw material further includes a Li source additive, and during the heating and reducing reaction, at least a part of the Li source in the Li source additive forms a lithium-silicon alloy with the silicon melt to obtain lithium-containing metallic silicon. Preferably, in this embodiment, the reducing agent is SiO 2 The amount of the additive added is such that the heating and reducing reaction of the ore particles is sufficiently carried out.
[0021] Preferably, in this embodiment, SiO 2 SiO in ore particles 2 The weight ratio of is 30 to 99 wt%, and / or SiO 2 The average particle size of the ore particles is 10 mm or less, more preferably 10 μm to 5 mm, and further preferably 30 μm to 3 mm.
[0022] Preferably, in this embodiment, the weight ratio of the Li source additive in the raw material is 0.05 to 35 wt%, more preferably 0.1 to 30 wt%, further preferably 1 to 20 wt%, and further preferably 5 to 10 wt%. Preferably, in this embodiment, the Li source additive is Li and / or Li 2 O and / or Li 2 CO 3 and / or LiOH and / or LiH and / or LiF and / or Li 2 SiO 4 (Li 2 SiO 2 , Lithium pentasilicate Li 2 SiO 5 , Lithium metasilicate Li 2 SiO 3 etc.) and / or a lithium alloy, and preferably, in this embodiment, the reducing agent includes a C source reducing agent, an Al source reducing agent, or an Mg source reducing agent, and SiO 2 They are used to carry out carbothermic, aluminothermic, and magnesothermic reduction reactions corresponding to ore particles, respectively.
[0023] The applicant uses a C source reducing agent as the preferred reducing agent, and SiO 2 It is proposed to carry out a carbothermal reduction reaction with the ore particles. Preferably, in this embodiment, the C source reducing agent can be selected from one or more mixtures of petroleum coke, pitch coke, charcoal, wood block, semi-coke, and low ash carbon. In addition, other known C source reducing agents can also be used. Preferably, in this embodiment, SiO 2In order to achieve sufficient heating and reduction of the ore particles, SiO 2 The weight ratio of the ore particles to the C source reducing agent is 1:1 to 6:1, more preferably 1.3:1 to 4:1, and further preferably 1.5:1 to 3:1.
[0024] Specifically, in this embodiment, it is proposed that the C source reducing agent contains a mixture of charcoal and low ash carbon, and the weight ratio of charcoal to low ash carbon is preferably 1:1 to 1:4, more preferably 1:1.5 to 1:3, and even more preferably 1:1.8 to 1:2.5, so as to promote the reduction effect.
[0025] Preferably, in this embodiment, SiO 2 The ore particles are lithium-containing SiO 2 Contains ore particles and lithium-containing SiO 2 The ore particles are obtained by crushing, screening and / or flotation of Li-bearing minerals, and preferably, in this embodiment, the Li-bearing minerals include lithium-bearing pyroxene and / or lithium mica and / or petalite and / or amblygonite and / or eucryptite, and may of course include other known Li-bearing minerals, all of which are within the scope of the present application.
[0026] In the examples of the present application, lithium-containing SiO 2 The preferred use of ore particles further contributes to the compatibility with the Li source additive during the thermal reduction reaction, and the lithium-silicon alloy formed by the silicon melt and the Li source (usually elemental Li metal) can be more stably distributed. More specifically, in actual practice, when metallic Li is used as the Li source additive, metallic Li can directly form a lithium-silicon alloy with the silicon melt, and when a lithium-containing compound is used as the Li source additive, it is reduced to elemental Li metal in the carbothermal reduction reaction atmosphere. In particular, Li 2 O, Li 2 CO 3 is a preferred Li source additive due to its high stability, but as pointed out in particular, Li 2O and / or Li 2 CO 3 When used as a Li source additive, Gibbs free energy was analyzed and it was found that under normal conditions, Li 2 O, Li 2 CO 3 However, the applicant discovered that under the extremely high temperature conditions in the reduction furnace, C and Si simultaneously act as reducing agents to produce Li. 2 CO 3 Li 2 O and CO 2 and the Li produced can be effectively reduced to 2 Li where O is not decomposed 2 CO 3 Enveloping Li 2 It was discovered that some of the O continues to react to form elemental Li metal and further forms a lithium-silicon alloy with the silicon melt, and that some of the unreacted lithium salt compounds penetrate in small amounts into the lithium-containing metallic silicon during the subsequent stocking process in the reduction furnace, further forming an alloy.
[0027] Preferably, the SiO in the reduction furnace 2 In order to promote the effect of the heating and reduction reaction between the ore particles and the reducing agent, in this embodiment, a known carbothermal reduction furnace can be used as a reaction device, and preferably, the electrode of the carbothermal reduction furnace is a graphite electrode or a carbon electrode, and the low-voltage side voltage is maintained at 80 to 190 KV, the current is 35,000 to 300,000 A, the electrode temperature is 2000 to 2400°C, and the amount of raw material supplied at one time may be controlled to about 100 KG, and a continuous reaction may be used, and the carbothermal reduction reaction time for one time may be 2 to 3 hours.
[0028] In the present embodiment, preferably, the melt of lithium-containing metallic silicon is transferred to an ingot-forming tank, and the melt in the ingot-forming tank is cooled, after which solid lithium-containing metallic silicon is obtained.
[0029] Preferably, in this embodiment, the lithium-containing metallic silicon is prepared by the preparation method described in this embodiment, and the lithium-containing metallic silicon contains lithium-silicon alloy and lithium silicate. In a specific implementation, the melt in the ingot casting tank is cooled, and then sampled and analyzed. The obtained product is lithium-containing metallic silicon, and the purity of the entire lithium-containing metallic silicon can be maintained at 95% or more, preferably 97% or more. The lithium contained in the lithium-containing metallic silicon exists in the form of a lithium-silicon alloy, and further, Li 2 SiO 2 and / or Li 2 SiO 4 and / or Li 2 SiO 5 and / or Li 2 SiO 3 and / or other lithium silicate forms, and the Li contained in the lithium-containing metallic silicon is uniformly distributed, reliable, and stable.
[0030] Preferably, the lithium-containing SiO is selected from the lithium-containing metallic silicon and SiO as described above in this embodiment. 2 The powder is used as a raw material, and at least a part of the lithium-containing metallic silicon is converted into SiO 2 The lithium-containing silicon metal powder is then subjected to a disproportionation sublimation reaction with the lithium-containing silicon metal powder to obtain lithium-containing SiO. More preferably, in the actual implementation, the lithium-containing silicon metal powder is first pulverized to obtain lithium-containing silicon metal powder, and the lithium-containing silicon metal powder is then subjected to a disproportionation sublimation reaction with the lithium-containing silicon metal powder. 2 After mixing the powders, the mixture is placed in a crucible, and the crucible is placed in a vacuum deposition furnace (the heating temperature range is controlled to 1000 to 1400°C) to carry out a disproportionation sublimation reaction. The lithium-containing SiO gas produced by the disproportionation sublimation reaction is placed in a condensation chamber and condensed to form a lump of lithium-containing SiO. In this embodiment, the lithium-containing metallic silicon powder preferably has an average particle size of 4 mm or less, more preferably 10 μm to 3 mm, and even more preferably 20 μm to 2 mm. The lithium-containing metallic silicon powder and SiO 2 The weight ratio of the powder may be selected to be about 1:2.
[0031] Preferably, in this embodiment, the lithium-containing SiO is pulverized to obtain the lithium-containing SiO powder, and at least a part of the outer surface of the lithium-containing SiO powder is coated with a carbon coating layer to obtain the lithium-containing SiO powder containing the carbon coating layer. Preferably, in this embodiment, the average particle size of the lithium-containing SiO powder is recommended to be 50 μm or less, and more preferably, is 2 to 30 μm. In this embodiment, the manufacturing process of the carbon coating layer can directly refer to the related publicly known process, and this embodiment is not particularly and uniquely limited, and specifically, the following examples can be mentioned.
[0032] The carbon coating layer of this embodiment may be prepared by uniformly mixing special asphalt, phenol resin, furfuryl alcohol, etc. with the lithium-containing SiO powder provided in the embodiment of this application, heating the mixture to 700 to 1000°C in an inert atmosphere, sintering the mixture, cooling the mixture, removing the mixture, and pulverizing and depolymerizing the mixture to complete the preparation. Alternatively, the lithium-containing SiO powder provided in the embodiment of this application may be placed in a shaking bed, fluidized bed, or vibrating bed, and methane, acetylene, propylene, ethanol vapor, inert gas, etc. are passed through the mixture to heat the mixture to 600 to 1000°C to perform a cracking reaction, and the mixture is cooled and removed to complete the preparation. Of course, the carbon coating layer of this embodiment may be prepared by other known methods, but the present application does not limit the method in any particular way.
[0033] Preferably, the application of the lithium-containing SiO as described above, the lithium-containing SiO powder with carbon coating layer is used as the active material raw material for preparing the negative electrode piece for battery, when specifically implemented, the preparation process of the negative electrode piece for battery can be any known process, this part does not correspond to the innovative content of the present application, and the present application does not limit it in any way.
[0034] In order to make those skilled in the art easily understand the technical solutions of the present invention, the following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention, and of course, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without requiring creative efforts shall be included in the protection scope of the present invention.
[0035] Example 1: Lithium-containing metallic silicon is prepared according to steps 1 to 6 below. In step 1, pegmatite containing spodumene and lithium mica is used as the raw material to produce lithium-containing SiO 2 Ore particles (their XRD scan images can be seen in FIG. 5) were obtained and detected to be lithium-containing SiO 2 The average particle size of the ore particles is about 1 mm, and SiO 2 It was confirmed that the weight ratio of was 70%.
[0036] In step 2, the lithium-containing SiO 2 Take 100 kg of ore particle raw material, and mix it uniformly with charcoal and low ash carbon as carbon-based reducing agents, the total weight of charcoal and low ash carbon is 40 kg, and the weight ratio of charcoal and low ash carbon is controlled to 32:68.
[0037] In step 3, the mixture obtained in step 2 is added with Li as a Li source additive. 2 CO 3 The weight ratio of the Li source additive in the entire mixed raw material is 6 wt %.
[0038] In step 4, the mixture obtained in step 3 is formed into lumps of suitable size (the specific size can be determined according to actual needs).
[0039] In step 5, referring to FIG. 1, the lump obtained in step 4 is put into a three-phase carbothermal reduction furnace, graphite electrodes or carbon electrodes are used as electrodes, the low-voltage side voltage is maintained at 80-190KV, the current is 35000-300000A, the electrode temperature is 2000-2400°C, the raw material supply amount per time is 100KG, continuous reaction is used, and the carbothermal reduction reaction time per time is 2-3h.
[0040] In step 6, referring to FIG. 2, after completing step 5, the silicon melt is collected in an ingot-forming tank, and the melt flow time is about 30 minutes. After cooling the silicon melt in the ingot-forming tank, a lithium-containing metal silicon finished product (the XRD scan image of which can be seen in FIG. 6) is obtained. After sampling and analysis, it is found that the obtained product is lithium-containing metal silicon with a purity of about 97%. The Li contained in the lithium-containing metal silicon is a lithium-silicon alloy, Li 2 SiO 2 , Li 2 SiO 4 , Li 2 SiO 5 , Li 2 SiO 3 It exists in the form of.
[0041] In the implementation of the present application, the size and shape of the lithium-containing metal silicon finished product can be selected according to actual needs, and can also be prepared as a lump lithium-containing metal silicon finished product, as shown in FIG. 3, which is not particularly limited in the present application.
[0042] Prepare lithium-containing SiO by following steps 7 to 8 below.
[0043] In step 7, the lithium-containing metallic silicon obtained in step 6 is pulverized to obtain lithium-containing metallic silicon powder having an average particle size of about 0.5 mm, and SiO 2 Mix uniformly with the powder in a 1:2 weight ratio.
[0044] In step 8, the mixture obtained in step 7 is placed in a crucible, which is then placed in a vacuum deposition furnace and heated to about 1200° C. to form a SiO2 The powder and lithium-containing metallic silicon powder are subjected to a disproportionation sublimation reaction, and the silicon monoxide (SiO) gas produced by the reaction is introduced into a condensation chamber where it is condensed and crystallized to obtain lump-shaped lithium-containing SiO (see Figure 7 for the XRD scan image).
[0045] Follow step 9 below to create a carbon coating layer.
[0046] In step 9, the lithium-containing SiO obtained in step 8 is pulverized to obtain lithium-containing SiO powder having an average particle size of about 15 μm, and the lithium-containing SiO powder is uniformly mixed with special asphalt, phenolic resin, and furfuryl alcohol, sintered under a temperature condition of heating up to 900°C in an inert atmosphere, cooled, taken out, pulverized, and depolymerized to obtain lithium-containing SiO powder (average particle size of 2 to 30 μm) including a carbon coating layer.
[0047] A negative electrode piece of a button battery is fabricated according to the following steps S10) to S70).
[0048] In S10), the lithium-containing SiO powder with a carbon coating layer obtained in step 9 is used as the active material, and CNTs, CMC, SBR, and SP are weighed out in that order as conductive agent excipients. The mixture is stirred at a speed of 600 r / min for 20 min using a mixer, and degassed for 5 min.
[0049] In S20), the active material and the conductive agent excipient SP:CNTs:CMC:SBR are mixed in a weight ratio of 80:15.85:0.15:2.5 to form a slurry, which is stirred at 600 r / min for 60 minutes using a mixer and degassed for 5 minutes.
[0050] In S30), the copper foil is cut to the size of A4 paper using a glass plate and placed flat with the inside side up on a semi-automatic coater, after which the slurry obtained in step S20) is further coated with a squeegee to form pole pieces.
[0051] In S40), heating is started after coating is completed, and the surface of the pole piece is dried, then transferred to a vacuum drying box and dried for about 6 hours.
[0052] In step S50, the dried pole pieces are taken out of the vacuum drying box, cut, and rolled. The rolled pole pieces are sliced with a button battery slicer into circular pole pieces with a diameter of 12 mm (see Figure 8 for the XRD scan image).
[0053] In S60), the circular electrode piece obtained in step S50) is weighed to be a negative electrode piece, and the negative electrode piece, lithium piece as a positive electrode piece, lithium piece separator, positive electrode case, negative electrode case, gasket, elastic piece, etc. are transferred to a glove box and assembled, the model of the battery case is 2032, the size of the lithium piece is 16mm*0.6mm, and the lithium piece separator is 19mm.
[0054] In S70), the assembled battery is transferred with tweezers to a sealing device for button batteries, and the battery is sealed.
[0055] In this application, tests were conducted on the button battery of Example 1 under the following test conditions:
[0056] The assembled battery is removed from the glove box and left at room temperature (23±2°C) for several hours to allow it to age, after which the battery is clamped into a test apparatus and tested under the following charge-discharge conditions:
[0057] The charge / discharge current is 0.1 C (1 C = 700 mA / g), the charge / discharge cutoff voltage range is 0.001 V to 1.5 V, and the battery is cycled five times under these charge / discharge conditions.
[0058] The capacity test graph of the button battery of this Example 1 is shown in FIG. 9 (where the abscissa of FIG. 9 is specific capacity and the ordinate is charge / discharge voltage), and the initial coulombic efficiency data of the battery is shown in Table 1 below.
[0059] [Table 1]
[0060] As can be seen from the table above, the initial coulombic efficiency of the button cell of Example 1 is 89.89%.
[0061] Example 2: In this example 2, the weight ratio of the Li source additive in the whole mixed raw material is 8wt%, except that the technical solution of this example 2 is the same as that of example 1.
[0062] Example 3: In this example 3, the weight ratio of Li source additive in the whole mixed raw material is 10wt%, except that the technical solution of this example 3 is the same as that of example 1.
[0063] Example 4: In this example 4, the weight ratio of the Li source additive in the whole mixed raw material is 2wt%, except that the technical solution of this example 4 is the same as that of example 1.
[0064] Example 5: In this example 5, the weight ratio of Li source additive in the whole mixed raw material is 1wt%, except that the technical solution of this example 5 is the same as that of example 1.
[0065] Example 6: In this Example 6, Li was used as the Li source additive. 2 Except for using O, the technical solution of this embodiment 6 is the same as that of embodiment 1.
[0066] Example 7: In this example 7, the technical solution of this example 7 is the same as that of example 1, except that metallic Li is used as the Li source additive.
[0067] Example 8: In this Example 8, LiF, Li were used as Li source additives. 2 SiO 4 Except for using 1:1, the technical solution of the present embodiment 8 is the same as that of embodiment 1.
[0068] Example 9: In this Example 9, the technical solution of this Example 9 is the same as that of Example 1, except that in step 1, petalite, amblygonite and eucryptite are used as the raw materials of Li-bearing minerals.
[0069] Example 10: In this Example 10, in step 1, SiO 2 Except for using ore, the technical solution of this embodiment 10 is the same as that of embodiment 1.
[0070] Example 11: In this Example 11, an Al source reducing agent was used instead of a C source reducing agent, and lithium-containing SiO 2 Except for generating the aluminum thermal reduction reaction with the ore particles, and making normal adjustments to the reaction conditions and reactor according to the actual reaction requirements to obtain silicon melt, the technical solution of this embodiment 11 is the same as that of embodiment 1.
[0071] Example 12: In this Example 12, a Mg source reducing agent was used instead of a C source reducing agent, and lithium-containing SiO 2 Except for generating the magnesium thermal reduction reaction with the ore particles, and making normal adjustments to the reaction conditions and reactor according to the actual reaction requirements to obtain silicon melt, the technical solution of this embodiment 12 is the same as that of embodiment 1.
[0072] When detected using the same detection conditions as in Example 1, the battery capacities of Examples 2 to 12 were maintained at 1200 to 1600 mAh / g, and the initial coulombic efficiency of the battery was 86 to 92%. Example 10 had a slightly lower battery capacity and initial coulombic efficiency than the other Examples, and therefore Example 10 is a sub-optimal Example compared to the other Examples.
[0073] Comparative Example 1: In this Comparative Example 1, the technical solution of this Comparative Example 1 is the same as that of Example 1, except that step 3 is omitted, and in step 4, the mixture obtained in step 2 is directly processed into chunks of suitable size.
[0074] When the detection was performed under the same detection conditions as in Example 1, the battery capacity was about 1000 mAh / g, and the initial coulombic efficiency of the battery was about 84%.
[0075] Comparative Example 2: In this Comparative Example 2, SiO was used as a raw material in step 1. 2 The technical solution of this Comparative Example 2 is the same as that of Example 1, except that ore is used, step 3 is omitted, and in step 4, the mixture obtained in step 2 is directly processed into suitable-sized chunks.
[0076] When the detection was performed under the same detection conditions as in Example 1, the battery capacity was about 550 mAh / g, and the initial coulombic efficiency of the battery was 70% or less.
[0077] Comparative Example 3: The technical solution of Example 1 in CN105789577A is adopted, and the process is difficult to implement and the operation risk is high.
[0078] When the detection was performed under the same detection conditions as in Example 1, the battery capacity was about 950 mAh / g, and the initial coulombic efficiency of the battery was about 79%.
[0079] Comparative Example 4: The technical solution of Example 1 in CN110993949A is adopted, and the process is difficult to implement and the operation risk is high.
[0080] When the detection was performed under the same detection conditions as in Example 1, the battery capacity was about 980 mAh / g, and the initial coulombic efficiency of the battery was about 87%.
[0081] By comparing the implementation effects of the above examples and comparative examples, it can be confirmed that the raw materials used in the examples of the present application are abundant and easy to obtain, and the cost is low, the preparation methods used are simple and easy to implement, which are conducive to large-scale production and application, and can reduce production risks, and Li in the obtained lithium-containing metallic silicon and lithium-containing SiO is uniformly distributed, and when the lithium-containing SiO with carbon coating layer provided in the examples of the present application is used as an active material raw material for preparing a negative electrode piece for a battery, the battery can exhibit higher capacity and initial Coulombic efficiency.
[0082] The present invention is not limited to the details of the above exemplary embodiments, and it is obvious to those skilled in the art that the present invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the present invention. The embodiments are therefore to be considered in all respects as illustrative and non-limiting, and the scope of the present invention is limited by the appended claims, not by the above description, and all modifications that come within the meaning and range of equivalent elements of the claims are intended to be embraced by the present invention. Reference numerals in the claims should not be considered as limiting the scope of the claims.
[0083] Furthermore, it should be understood that although the present specification is described according to the embodiments, each embodiment does not include only one separate technical solution, and such description manner in the present specification is merely for the purpose of clarifying the description, and those skilled in the art should take the specification as a whole, and the technical solutions of each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. The raw material is SiO 2 Contains ore particles and a reducing agent, and SiO 2 At least a portion of the ore particles and the reducing agent are subjected to a heating and reducing reaction in a reduction furnace to obtain a silicon melt, the raw material further contains a Li source additive, and during the heating and reducing reaction, at least a portion of the Li source in the Li source additive forms a lithium-silicon alloy with the silicon melt to obtain lithium-containing metallic silicon, and the SiO 2 The ore particles are lithium-containing SiO 2 The lithium-containing SiO 2 A method for preparing lithium-containing silicon metal, characterized in that ore particles are obtained by crushing, sorting and / or flotation of a Li-containing mineral, the Li-containing mineral includes lithium-containing pyroxene and / or lithium mica and / or petalite and / or amblygonite and / or eucryptite, the weight ratio of the Li source additive in the raw material is 0.05 to 35 wt %, and the lithium-containing silicon metal includes a lithium-silicon alloy and a lithium silicate salt.
2. The SiO 2 SiO in ore particles 2 The preparation method according to claim 1, characterized in that the weight ratio of is 30-99 wt%.
3. The SiO 2 2. The method according to claim 1, characterized in that the average particle size of the ore particles is less than 10 mm.
4. The Li source additive is Li and / or Li 2 O and / or Li 2 CO 3 and / or LiOH and / or LiH and / or LiF and / or Li 2 SiO 4 and / or a lithium alloy.
5. The reducing agent includes a C source reducing agent, an Al source reducing agent, or an Mg source reducing agent, and the SiO 2 2. The preparation method according to claim 1, which is used to carry out carbothermic reduction, aluminothermic reduction and magnesothermic reduction reactions with corresponding ore particles, respectively.
6. The method according to claim 1, characterized in that the melt of the lithium-containing metallic silicon is transferred to an ingot-forming vessel, and the melt in the ingot-forming vessel is cooled to obtain a solid lithium-containing metallic silicon.
7. The lithium-containing metallic silicon and SiO2 powder prepared by the method according to claim 1 are used as raw materials, and at least a part of the lithium-containing metallic silicon is converted into the SiO2 powder. 2 A method for preparing lithium-containing SiO, comprising the steps of: subjecting a lithium-containing SiO powder to a disproportionation sublimation reaction to obtain lithium-containing SiO.
8. The lithium-containing metal silicon is crushed in advance to obtain lithium-containing metal silicon powder, and the lithium-containing metal silicon powder and the SiO 2 The powders are mixed and then placed in a crucible, the crucible is placed in a vacuum deposition furnace to carry out the disproportionation sublimation reaction, and the lithium-containing SiO gas produced by the disproportionation sublimation reaction is condensed to form a lump of lithium-containing SiO. The method for preparing the lithium-containing SiO according to claim 7.
9. The lithium-containing SiO is pulverized to obtain a lithium-containing SiO powder, and at least a part of the outer surface of the lithium-containing SiO powder is coated with a carbon coating layer to obtain a lithium-containing SiO powder including a carbon coating layer. The method for preparing the lithium-containing SiO according to claim 7.
10. A method for producing a negative electrode piece for a lithium ion battery, comprising using a lithium-containing SiO powder containing a carbon coating layer prepared by the method of claim 9 as an active material raw material for producing a negative electrode piece for a battery.
Citation Information
Patent Citations
Negative electrode active material for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, method for manufacturing negative electrode material for nonaqueous electrolyte secondary battery, and method for manufacturing nonaqueous electrolyte secondary battery
JP2017073302A
Negative electrode material
JP2018152161A
Silicon oxide negative electrode material and production method therefor
WO2018074175A1